Psychometric Evidence of the Scale of Risk of Addiction to Social Networks and Internet for Adolescents in Peruvian Students - Gamboa-Melgar, Goldie (2022)
The aim of the study was to analyze the psychometric properties of the Adolescent- Risk of Addiction to Social Networks and Internet Scale (ERA-RSI) in Peruvian students. The sample was composed by 755 students (52.2% women), whose ages ranged from 13 to 24 years (M = 17, SD = 2.93) and attended private schools (62.2%) or universities (33.8%). The internal structure of the ERA-RSI, the invariance according to the level of instruction and sex, its relationship with other variables, and the reliability by internal consistency were analyzed. The results of the Confirmatory Factor Analysis (CFA) indicate a four-dimensional structure with adequate fit indices (χ2 / gl = 3.81, CFI = .91, TLI = .90, RMSEA = .061 [.058, .065], SRMR = .061) and which is invariant according to the level of instruction (school and university) and sex (men and women). In addition, good reliability is shown by internal consistency (ω = .74 to .83). For its part, convergent validity was performed with the Social Media Addiction Questionnaire (ARS) a positive, moderate to strong statistically significant correlation were found between the dimensions of both tests. In conclusion, the present adaptation of the ERA-RSI has, in general, adequate empirical evidence of validity and reliability and can be used in future research.